Psychological suffering, academic perception and associated factors among undergraduate students during the COVID-19 pandemic - Pap da Silva, Emanuela (2025)
Introduction: The high prevalence of Common Mental Disorders (CMD) among university students, especially during the Covid-19 pandemic, indicates the relevance of studies addressing mental health of this group. Objective: This study presents the institutional mapping carried out by the student support and psychological services of a Brazilian university in São Carlos/SP, aiming to identify the mental health of its students. Method: A self-administered questionnaire was used, consisting of a sociodemographic inventory and scales of academic perception to collect data from September to October 2021 campus-wide. Results: Out of 5.121 undergraduate students at that time, 340 responded to the questionnaire, and 73,24% screened positive for CMD. The highest prevalence was among students who entered in 2018 or earlier (81%), possibly due to the transition to Distance Learning (DL) during the pandemic. Additionally, the prevalence of CMD increases with age, suggesting an impact of entering university during the pandemic. Discussion: Among possible actions, it is essential to create spaces for emotional expression, develop individual and collective resources, prepare the academic community to identify vulnerabilities and their interventions, and approach institutional determinants of psychological distress through periodic scientifically based data collection.